Secondary Flow for Slow Rotation of a Pervious Sphere with Source at its Centre in a Viscous Fluid - Awasthi, Mukesh; Mani, Naveen; Sharma, Amit; Shukla, Rahul (IndoMS, 2025)
In this paper, the problem of secondary motion of fluid in region between two concentric spheres are studied. Navier Stokes equations are employed to obtain the flow field, and the components of velocity for primary and secondary flow, stream function are obtained. Further, two particular cases are deduced and discussed for the radius of cavity. Finally, Equi-pressure lines, streamlines, and vortex lines are constructed to visually demonstrate the impact of different factors on the flow pattern.